Separating introduction effects from selectivity effects: The differences in employment patterns of co-determined firms - Rafael Gralla; Kornelius Kraft (Institute for the Study of Labor (IZA), 2012)
This study examines differences in employment growth between firms with and without works councils by separating introduction effects from potential selectivity effects. Using a difference in differences framework, we show that firms with works councils have higher employment growth before establishing a works council. However, employment growth declines after introduction. We identify the reason for lower employment growth in reduced hiring rates but constant dismissal rates.
Keywords: J53; J63; C23; M54; 330; works councils; hires; dismissals; employment growth; difference-in-differences; Betriebsrat; Mitbestimmung; Beschäftigungseffekt; Deutschland